2007
DOI: 10.1097/01.mlg.0000231281.76358.cc
|View full text |Cite
|
Sign up to set email alerts
|

Osseointegration Timing for Baha System Loading

Abstract: The reduction of the waiting period from 3 months to 6 weeks did not result in any failure of osseointegration of the titanium implants. The earlier activation resulted in enhanced patient satisfaction. A larger series would be needed to definitively recommend shortening of the interval between Baha implantation and device loading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 12 publications
(12 reference statements)
2
31
0
Order By: Relevance
“…Although the potential for increased skin reactions and excess bone formation has traditionally been considered higher in children, in our study, we found it was comparable with other recent pediatric studies (1,29,30) and actually less than some previous adult reports (30).…”
Section: Discussionsupporting
confidence: 91%
“…Although the potential for increased skin reactions and excess bone formation has traditionally been considered higher in children, in our study, we found it was comparable with other recent pediatric studies (1,29,30) and actually less than some previous adult reports (30).…”
Section: Discussionsupporting
confidence: 91%
“…A pilot study on the waiting time for Baha loading revealed no increased extrusion rate for patients with implants loaded 6 weeks postoperatively compared to those loaded 3 months postoperatively (14). All adult patients implanted by the senior author since 2002 have received their processor at 6 weeks with no implant losses.…”
Section: Discussionmentioning
confidence: 98%
“…In the one-stage procedure, the implant and abutment are placed at the same time, whereas in the two-stage procedure, the abutment is fitted after a period of around 3 months in adults or 4-6 months in children to allow osseointegration (where bone fuses with the implant) to occur. 51 The advantage of one-stage surgery is that it requires only one surgical procedure, but it risks transmission of forces through the abutment to the fixture before osseointegration has occurred, resulting in a failure of osseointegration and loss of the fixture. The two-stage procedure is therefore most commonly used for young children, adults who may not be able to protect the abutment adequately (e.g.…”
Section: Interventionmentioning
confidence: 99%